PET studies on amino acid metabolism and protein synthesis : proceedings of a workshop held in Lyon, France within the framework of the European Community medical and public health research - Mazoyer, B. M.; Heiss, Wolf-Dieter; Comar, D. (Dordrecht : Kluwer Academic Publishers, 1993)
Parameters such as membrane transport, metabolism and protein incorporation govern the fate of amino acids in living tissue. Is it possible to use positron tomography to measure some of them, and what is their meaning in normal and pathological situations? These questions have been addressed for a long time and no satisfactory answer has yet been given. This book, which derives from an EEC workshop organized in the frame of the Concerted Action on `PET Investigation of Cellular Regeneration and Degeneration', held in Lyon in February 1992, gives the present state of knowledge in this field based on the most recent studies. Contributions from 24 leading European and American scientists are presented and discussed in the following four parts: biochemistry and animal studies; amino acids labelling with positron emittors, quality control and metabolites measurement; kinetic modelling of amino acids transport, metabolism, and protein incorporation; clinical use of amino acids. This book will aid and interest biochemists, radiochemists, pharmacologists, neurologists, oncologists and medical imaging scientists.
Bibliogr. odkazy
Keywords: tomografia pozitrónová emisná -- metódy -- štatistika a číselné údaje; aminokyseliny -- metabolizmus; biosyntéza proteínov; PET Investigation of Cellular Regeneration and Degenaration, Lyon, 1992; zborník